LIBRARY USE BY STUDENTS OF AKROPONG SCHOOL FOR THE BLIND, EASTERN REGION, GHANA - Appiah, D. K. (UDS International Journal of Development, 2019)
The aim of this study was to investigate the provision of library services to visually - challenged students at Akropong School for the Blind in the Eastern Region of Ghana. A mixed methodology was used as the research design. The study population was sixty-seven. All the JHS 1 to 3 students of the school were issued with copies of a questionnaire in braille format while two Library staff and the Headmaster of the School were interviewed. Quantitative data was analyzed using the Statistical Package of Social Sciences (SPSS) while qualitative data was analyzed thematically. The study reveals the lack of policy in providing information services to visually - challenged students, lack of assistive technology devices, lack of braille textbooks, inadequate library resources and the library being too small to accommodate even two classes. The study recommended that assistive technology devices such as voice recognition software, screen magnifier and computer with JAWS are needed for visually challenged students. It is further recommended that, the School authorities should appeal to the Parent/Teacher Association, the District Assembly and other philanthropic organizations to expand the Library to make it more accommodating for the student population. The School was found to be doing a good job of providing a welcoming library environment for the students. It still has a lot of work to accomplish to create an enabling environment for the visually - challenged students. The Library should also enhance services delivery tailored for visually challenged students. Keywords: Visually - Challenged Students, Library Resources, Library Services, Assistive Technology Devices, Special Needs